A Partial Coherent Interferometry for measuring the thickness of a dynamic liquid sheet. (July 2019) - Shang, Weixiao; Chen, Jun
Highlights: Develop a new non-invasive method for measuring the thickness distribution of a dynamic liquid sheet. Relate the degree of coherence and the optical path difference to the thickness of the sheet. Verify the method by applying it to a glass sample and a static ethanol film. Measure the dynamic impinging sheet formed by the two ethanol jets. The thickness distribution ranges from 26 to 38 µm. Abstract: This work presents a non-invasive technique, Partial Coherent Interferometry, for measuring the thickness distribution of a dynamic liquid sheet. It utilizes the linear relationship between the degree of coherence and the optical path difference to determine the thickness of the sheet. In an interferometer using a partial coherent laser, the interference patterns before and after the liquid sheet insertion are digitally recorded. The relative thickness distribution is determined by applying a phase unwrapping process to the recorded interference pattern. By measuring the change of the degree of coherence introduced by the sheet, the absolute thicknesses at the reference points are determined. By matching the relative thickness to the absolute thicknesses at different points, the absolute thickness distribution is retrieved. To verify the reliability of this method, a glass sample and a static ethanol film, both with nominal thicknesses (152.4 µm), are measured first. The results, a nearly uniform thickness of 148.8 ± 1.8 µm for glass and a varying thickness distribution around 154.6 µm for static ethanol film, show the capability of this method to measure a two-dimensional thickness distribution of a thin liquid sheet. Then a dynamic impinging sheet formed by the two ethanol jets with Reynolds number 763 and Weber number 143 is measured by Partial Coherent Interferometry. The thickness distribution ranges from 26 to 38 µm with an uncertainty of 2.1 µm.